TATOPSIS: A decision support system for selecting a major in university with a two-way approach and TOPSIS - Dewi Wardani; Widyaswari Mahayanti; Haryono Setiadi; Maria Ulfa; Endar Wihidayat (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2022)
Several problems can occur when students feel they have made the wrong choice of major in university. Choosing a major is one of the problems that students often face. Therefore, this study aims to develop a Decision Support System (DSS) to help students find majors that match their interests and abilities. This DSS proposes a two-way approach by considering students and the major's requirements, standards, and characteristics. The DSS utilizes the TOPSIS method; therefore, it is called TATOPSIS, which stands for Two-way Approach TOPSIS. It showed that the two-way approach in Scenario 1 (without score normalization) and Scenario 3 (with score normalization) shows better agreement results in 78.33% and 73.33% than the two-way approach for Scenario 2, Scenario 4, and the student-one-way approaches.